Friction stir processing for enhanced low temperature formability - Smith, Christopher B.; Mishra, Rajiv S. (Butterworth-Heinemann, 2014)
The use of friction stir processing to locally modify the microstructure to enhanced formability has the potential to alter the manufacturing of structural shapes. One example of a conventional manufacturing technique for aluminum alloys involves fusion welding of 5XXX series alloys. This can be replaced by friction stir welding, friction stir processing and forming resulting in the advantage of enhanced properties. This book provides a case study of Al5083 alloy with some additional examples of high strength aluminum alloys. It demonstrates how friction stir processing enabled forming can expand the design space by using thick sheet/plate for applications where pieces are joined because of lack of formability; opens up new method for manufacturing of structural shapes; and shows how the process has the potential to lower the cost of a finished structure and enhance the design allowables. --
Includes bibliographical references
Keywords: TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades; Friction stir welding; Machining; Metals / Formability; Technology; Metals -- Formability; Machining -- Handbooks, manuals, etc